IMPLEMENTING WRITING PROCESS APPROACH WITH PICTURES TO IMPROVE THE ABILITY OF THE EIGHTH GRADES IN WRITING RECOUNTS - Muhammad Lukman Syafii (Universitas Islam Negeri Alauddin Makassar, 2019)
Writing skill has an important role in the English teaching program in Islamic Junior High School. However, the ability of the eighth-graders of this school in writing is still dissatisfactory. The students feel still difficulties how to start writing and they don’t have an idea to write. This research is intended to progress the writing skill of the eighth graders by implementing a writing process approach with pictures. This strategy is chosen since it can lead the students to generate their ideas into a useful composition. The findings in the preliminary study show that the students need to learn how to start their writing and they do not have ideas to write. Only 8 of 31 students achieve the average score of writing skill equal to or above 70. To get the purpose, the researcher conducted action research following four steps: planning, implementing, observing, and reflecting. The subject of the study were 31 students of the eighth grade. The findings show that implementing a writing process approach with pictures has progressed the writing skill of students. In cycle one, the students’ average score was 15 of 31 failed and 16 of 31 students passed or got the score equal or greater than 70. In cycle two, the average score for the final product was 6 of 31 students failed and 25 of 31 students passed or got the score equal or greater than 70. Also, the findings of students revealed that the students’ participation was active and motivated using pictures in the teaching and learning activities. Based on the results, it can be summarized that implementing a writing process approach with pictures is very beneficial not only in progressing the students’ writing skill but also in motivating the students in the learning activities.Keywords: using pictures, writing skill, recount text